The Influence Of Leadership And Supervision Of Employee Performance In The Employee Cooperatives PT. Purna Baja Harsco Cilegon - Rt. Erlina Gentari (Ilomata International Journal of Management, 2021)
Good leadership and supervision of employees are some of the factors that are expected to improve employee performance at PT. Purna Baja Harsco Cilegon. This study aims to find out how much influence leadership and supervision have on employee performance at PT. Purna Baja Harsco Cilegon. The population and sample in this study were all employees totaling 99 employees who worked at PT. Purna Baja Harsco Cilegon. This research was conducted from 03 to 15 November 2019. Data were collected by questionnaire method, and the analysis used was the data instrument test, classical assumption test, multiple regression analysis, coefficient of determination, and hypothesis testing using SPSS v.25 for windows. Based on the results of this study concluded that: Hypothesis 1 test obtained tvalue is greater than ttable (5,242 > 1,984) so ​​H0 is rejected and H1 is accepted which means leadership (X1) influences employee performance (Y), hypothesis 2 obtained tvalue is greater than ttable ( 6,597 > 1,984) so ​​that H0 is rejected and H1 is accepted which means supervision (X2) influences employee performance (Y), and hypothesis 3 is obtained the Fvalue value is 638,205 while Ftable is 3.09 which means Fvalue > Ftable. This shows that H0 is rejected and H3 is accepted, which means that leadership (X1) and supervision (X2) jointly influence employee performance (Y).